Flavanones: A potential natural inhibitor of the ATP binding site of PknG of Mycobacterium tuberculosis. Issue 22 (12th December 2022) - Swain, Supriya P.; Gupta, Subhi; Das, Nidhi; Franca, Tanos Celmar Costa; Goncalves, Arlan da Silva; Ramalho, Teodorico Castro; Subrahmanya, Shreya; Narsaria, Utkarsh; Deb, Debashrito; Mishra, Neelam
Abstract: Over the years, Mycobacterium tuberculosis has been one of the major causes of death worldwide. As several clinical isolates of the bacteria have developed drug resistance against the target sites of the current therapeutic agents, the development of a novel drug is the pressing priority. According to recent studies on Mycobacterium tuberculosis, ATP binding sites of Mycobacterium tuberculosis serine/threonine protein kinases (MTPKs) have been identified as the new promising drug target. Among the several other protein kinases (PKs), Protein kinase G (PknG) was selected for the study because of its crucial role in modulating bacterium's metabolism to survive in host macrophages. In this work, we have focused on the H37Rv strain of Mycobacterium tuberculosis. A list of 477 flavanones obtained from the PubChem database was docked one by one against the crystallized and refined structure of PknG by in-silico techniques. Initially, potential inhibitors were narrowed down by preliminary docking. Flavanones were then selected using binding energies ranging from −7.9 kcal.mol −1 to −10.8 kcal.mol −1. This was followed by drug-likeness prediction, redocking analysis, and molecular dynamics simulations. Here, we have used experimentally confirmed drug AX20017 as a reference to determine candidate compounds that can act as potential inhibitors for PknG. PubChem165506, PubChem242065, PubChem688859, PubChem101367767, PubChem3534982, and PubChem42607933 were identified as possible target site inhibitors for PknG with a desirable negative binding energy of −8.1, −8.3, −8.4, −8.8, −8.6 and −7.9 kcal.mol −1 respectively. Communicated by Ramaswamy H. Sarma